Effect of Demographic Factors on Consumer Buying Behaviour of Durable Goods - Juyal, Som Aditya (Indian Journal of Marketing, 2013)
The size of the consumer market in the country is vast and is constantly expanding. Billions of rupees are being spent on goods and services by millions of people. Consumer preferences are changing and are becoming highly diversified. At present, the demands for various consumer products are increasing day by day. In the markets, where the magnitude of competition is high, a marketer will be successful only when s/he identifies, analyzes, and responds suitably to the changing needs of the consumers. Holding this view, this study pertains to the assessment of the product uses and brand preferences among durables and ascertaining the sources of information, buying habits, and factors affecting product/brand choice of the consumer with respect to their demographic profiles. The durables considered for the study are limited to personal utilities - mobile phone and two-wheeler and home utilities - colour television, washing machine, and refrigerator. The demographic factors with reference to this study include age, gender, marital status, education, occupation, and income. A sample of 610 respondents from Dehradun District were surveyed using a self administered questionnaire. The statistical measures used for the study includes chi-square and t -test. Statistical test indicates support for significant and influence of demographics on consumer purchasing behavior. Limitations of this study include the use of convenience sampling and confinement to the selected branded consumer durables.